Molecular profiling of Peru Balsam reveals active ingredients responsible for its pharmaceutical properties. Issue 23 (2nd December 2021) - Riesmeier, Marabel; Mattonai, Marco; Wong, Szu Shen; Veall, Margaret-Ashley; Betts, John; Johnston, Matthew; Ribechini, Erika; Devièse, Thibaut
Abstract: Peru Balsam, a resinous substance derived from Myroxylon balsamum var. pereirae, has historically been used as a topical ointment for various skin conditions such as scabies, poorly healing wounds, eczema, and haemorrhoids. The ingredients responsible for these properties are not fully elucidated. We investigated the chemical composition of two Peru Balsam samples, one historical and one modern, using gas chromatography/mass spectrometry to identify the active ingredients responsible for its pharmaceutical properties. Both Peru Balsam specimens investigated had similar compositions, showing the stability of the substance. Components identified are effective against scabies, exhibit antimicrobial activity and aid skin penetration. These properties are consistent with historical uses of Peru Balsam. Several ingredients are also known allergens. This study, combining chemical information with scientific literature related to pharmaceutical properties of natural substances, represents a breakthrough in the elucidation of active ingredients in Peru Balsam. Graphical Abstract: